2014
DOI: 10.1007/s10903-014-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Traumatic Experiences Among Asylum Seekers from Eritrea and Sudan During Migration to Israel

Abstract: Little is known about the experiences of displaced individuals en route to destination countries. We investigated the reported prevalence of exposure to traumatic experiences during migration among a consecutive sample of adult asylum seekers (n = 895 Eritrean, n = 149 Sudanese) who sought health services in the Physicians for Human Rights Open-Clinic in Israel. Percentage of Eritrean and Sudanese men and women who reported witnessing violence (Eritrea: men: 41.3 %, women: 29.3 %; Sudan: men: 16.8 %, women: 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 27 publications
4
28
1
1
Order By: Relevance
“…Additionally, MHA may lack family support, as the majority are single. Some may suffer from post-traumatic stress disorders due to harassments and attacks they experienced during their terrestrial voyage to Israel [14]. Interestingly, we did not find association between the country of origin and the severity of disease or the need for further referral to secondary and tertiary health care.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Additionally, MHA may lack family support, as the majority are single. Some may suffer from post-traumatic stress disorders due to harassments and attacks they experienced during their terrestrial voyage to Israel [14]. Interestingly, we did not find association between the country of origin and the severity of disease or the need for further referral to secondary and tertiary health care.…”
Section: Discussioncontrasting
confidence: 60%
“…Yet, a greater proportion of women were referred to other medical settings, as a result of a greater need for gynecological care, which had not been available fully at the clinics. A recent publication from Israel has suggested that MHA have high rates of psychological problems as a result of stress and assault they experienced during their voyage to Israel [14]. It is therefore recommended that the clinics include gynecological and psychological secondary care consultation to meet the medical needs of the migrants.…”
Section: Discussionmentioning
confidence: 99%
“…However, as our study shows, one should also note substantial prevalence of symptoms potentially associated with mental health needs. These may be related to experiences before, during and after migration [ 16 , 17 ]. With regard to post-migration risk factors, our findings support prior studies [ 14 ] showing that precarious employment and the related social insecurity are major stressors in the lives of many asylum seekers, compounding the threats related to living in legal instability and a largely hostile environment.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, Palestinian medical facilities in East Jerusalem offer comparably inexpensive rates [ 14 , 15 ]; yet accessing them can be problematic in terms of time and travel costs. The few existing studies on the health of asylum seekers in Israel point to considerable delays in treatment onset [ 12 , 14 ] and substantial unmet reproductive and mental healthcare needs [ 16 , 17 ]. A special report by the State Comptroller [ 10 ] notes that “without adequate health care in the community the medical needs of some of the non-deportable foreigners are neglected until they become matters of emergency care.” (p.63) It further points out that “[t] he absence of [corresponding] budgetary resources is liable to harm also the hospitals’ economic stability” (ibid.)…”
Section: Introductionmentioning
confidence: 99%
“…Siehe auch den ausführlichen Bericht von Amnesty International "Forced and Unlawful" (2018) (https://www.amnesty.org/download/Documents/MDE1584792018ENGLISH.PDF, S. 32 <02.03. 2020>).17 Vgl Nakash et al (2014). sowie detailliert: Human Rights Watch (2014): Human Trafficking in the Sinai: Refugees between Life and Death, https://www.hrw.org/report/2014/02/11/i-wanted-liedown-and-die/trafficking-and-torture-eritreans-sudan-and-egypt <03.03.2020>.…”
unclassified